Gaya Berpakaian Crop Top Pada Kalangan Mahasiswi Universitas Jember Untuk Pengelolaan Kesan dalam Tinjauan Teori Dramaturgi Erving Goffman - Anakku Saviola; Dava Putratama; Fery Febriansyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Clothing is a significant influence on the development of fashion trends today which most people follow with the desire to look trendy and fashionable. Crop top is one type of clothing that is most widely used as an outfit, especially for young people. Today's women are individuals who are very fond of making fashion changes to keep up with increasingly advanced developments, and crop top make most of them confident users, even like clothing in general nowadays. The aim of this research is to find out how clothing styles are influenced by increasingly rapid developments and how crop top clothing is used as a front stage for women and a back stage in the real lives of women who wear crop top clothing today. The method used is a qualitative method, data collection through in-depth interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. This research uses Erving Goffman's Dramaturgical theory. The results of the research show that Jember University students who are fans of the crop top style of clothing have reasons to get an impression from the general public in order to gain an image as a representative of today's trendy kids. So that makes them acceptable in society, but what is surprising is that the reality they have behind the public is not like what is seen on the surface. The risks that arise from this way of dressing are very diverse because the style of clothing creates an increased risk of crime.